Power-type strength training in middle-aged men and women - Surakka, J. (Journal of Sports Science & Medicine, 2005)
Muscle strength declines with increasing age, and the power-type strength characteristics decline even more drastically than the maximal muscle strength. Therefore, it is important to design training programmes specifically for sedentary middle-aged people to effectively improve the power-type strength in leg and trunk muscles. To be suitable for the target group, the exercise programmes should be feasible, motivating and easy to practice. The aim of this study was to design and investigate the effects and feasibility of a power-type strength training programme in 226 middle-aged men and women, with 26 persons as non-training controls. The subjects trained three times a week during 22 weeks, in 12 groups with exercise classes of 10-20 subjects, and using no or very little external equipment. All training sessions were controlled and supervised by an professional instructor. Vertical squat jump, standing long jump, 20 metre running time, maximal anaerobic cycling power, maximal oxygen uptake, and angular trunk muscle flexion and extension velocities were measured before and after the training period to evaluate the training effects. Questionnaires concerning employment, physical activity, smoking, musculoskeletal symptoms and exercise motives were also filled in before and after the training period. The greatest improvements were achieved in vertical squat jump (18%) and in angular trunk flexion (14%) and extension (16%) velocities. An external loading totalling 2.2 kg (attached) in ankles increased the height in vertical squat jump by 23% and maximal anaerobic cycling power by 12%, these improvements were significant compared with subjects in no load training group (p = 0.03 in vertical squat jump and p = 0.05 in maximal anaerobic cycling power). Exercise induced injuries occurred in 19% of men and 6% of women. Low back symptoms decreased in exercisers by 12% and knee symptoms (increased) by 4% during the intervention. Of all subjects, 24% dropped out during the training period. In summary, improvements were achieved in several physiological performances reflecting the power-type strength qualities, especially in vertical squat jump and trunk muscle flexion and extension velocities. Improved perceived health and fitness among the participants who completed the training programme, and the relatively low number of injuries also indicate the feasibility of the programme. The training programme is simple, and it also seems to be practical among middle-aged, sedentary subjects. It may be useful in preventing the decline of power-type strength characteristics in middle-aged subjects.